An Analytical Study of "Flight in the Cage" - Dr. Rehana kausar (Corresponding Author); Dr. Shaista Hameed Khan (Al-Qanṭara, 2024)
Flight in a Cage is a story of a spiritual journey. It is described as an ideal story. The author mentioned very important Sufi points which described in the metaphorical style. In the story, the poems of Sufi poets, sayings and references of elders are presented, such as the great Sufi leader Hazrat Inayat Khan, Hazrat Baba Bulhe Shah, Hazrat Shah Hussain and Hazrat sultan baho.